MODELING OF BUSINESS PROCESSES OF HIGHER EDUCATION INSTITUTION AT INTRODUCTION OF PROCESS MANAGEMENT - Svetlana L. Bedrina; Olga B. Bogdanova; Elena V. Kiykova; Galina L. Ovsyannikova (Открытое образование (Москва))
The article considers transition questions to process management of higher education institution, specifics of educational process and is specified possibilities which are received by heads and the staff of university, when using modeling of business processes. The author's technique of the description of business processes of higher education institution is depicted in the article. The detailed description of each stage is provided, templates of used models and documents are described.